Small molecule gas adsorption onto blue phosphorene oxide layers (2020)
We report a first-principles study of the electronic and optical properties of BPO (Blue phosphorene oxide) and BPO-V (Blue phosphorene oxide with vacancy) with the adsorption of low molecular weight gases (CH4, CO2, CO, SO2, and O2). Blue phosphorene oxide -with and without vacancies- shows different optoelectronic compared to blue phosphorene. The BPO has proven to be more energetically, and structurally stable than blue phosphorene under ambient conditions. Our calculations show that: Blue phosphorene oxide -with and without vacancies- exhibits different optoelectronic compared to blue phosphorene. Physical adsorption occurs for all gas molecules. Highest values of adsorption energy are found when the monolayers interact with O2 and SO2. This is associated with a modification of conducting nature, which is changed from semiconductor to conductor character, depending on the orientation of adsorbed molecules. By contrast, the coupling with CO and CO2 molecules leads to the lowest values of the energy of adsorption. The observed features of the electronic properties and optical response of BPO + adsorbed-gas complexes allow to suggest that this phosphorene-based structures could be promising candidates for gas sensing applications. © 2020 Elsevier B.V.